Attracting children’s attention to literature through the object of project activity-table theater - Olga V. Kaukina; Anastasia A. Erastova (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
Today, there are many electronic devices that can replace the things we are used to. Todays children and adolescents spend more and more time learning new means of communication and searching for information, which is why traditional means (books, communication, experience) take a back seat and eventually become less important for overall development. While studying in primary school, it is easier for children to work with Internet sources because of the simplicity and conciseness of information that is in General use. Reading material from a book is replaced by gadgets. The very concept of reading has acquired a different meaning, has ceased to be a part of culture. Many parents and teachers face this problem when trying to teach their children to read literature. The purpose of this project is to find an alternative way to attract children to literary works through the object of project activity-table theater for children.